The Colonial Legacies of the Digital Archive: The Arnold Lupson Photographic Collection - Opp, James (Archivaria, 2008)
This article explores the transformative ef fects of digitization on photographs by tracing the history of one series of photographic images, the Arnold Lupson collection, at the Glenbow Archives in Calgary, Alberta. As Lupson’s photographs of First Nations peoples, originally taken in the 1920s, moved through dif ferent hands and archival grids, the meanings attached to the photographs were reworked and renegotiated, and remnants of these earlier interventions continue to haunt the digital databases that now bear the cultural weight of these photographs. It is ar gued that in order to fully grasp these colonial legacies, we need to be able to reconnect the material history of the photographs more overtly to their virtual surrogates. RÉSUMÉ Ce texte explore les effets transformateurs de la numérisation sur les photographies en examinant l’histoire d’une série d’images photographiques, la collection Arnold Lupson, déposée aux Archives Glenbow à Calgary, en Alberta. Les photographies de Lupson, qui ont été prises dans les années 1920, montrent des peuples des Premières Nations. Au cours des années, des personnes travaillant selon différents courants archivistiques ont laissé leur marque sur les descriptions de ces photographies, qui ont été retravaillées et modifiées. Des vestiges de ces premiers efforts descriptifs paraissent toujours dans les bases de données numériques qui portent maintenant la marque culturelle de ces photographies. Le texte conclut que pour mieux comprendre cet héritage colonial, nous devons être capables de faire le lien plus ouvertement entre l’histoire matérielle de ces photographies et leurs copies virtuelles.